Aliphatic-aromatic copolyester material as well as preparation method and application thereof
By using precipitated fat-aromatic copolyester II as a nucleating agent in fat-aromatic copolyester materials, the problem of poor crystallization effect of the material under rapid cooling conditions is solved, and the gas barrier and transparency are significantly improved, meeting the application needs of packaging materials and mulch films.
Patent Information
- Application Number
- CN202311378971.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing fat-aromatic copolyester materials have poor crystallization effect under rapid cooling conditions, and lack gas barrier properties and transparency, making it difficult to meet the application needs of packaging materials and mulch films.
The fat-aromatic copolyester I and the precipitated fat-aromatic copolyester II are melt-mixed as the nucleating agent to form a self-nucleating agent to promote crystallization and improve gas barrier properties and transparency.
Under rapid cooling conditions, fat-aromatic copolyester materials can quickly crystallize, improve processability, and significantly improve gas barrier and transparency. They are suitable for packaging materials and plastic films and other fields.
Smart Images

Figure CN119875318A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a biodegradable polymer material, in particular to a fat-aromatic copolyester material, a preparation method and application of the fat-aromatic copolyester material. Background Art
[0002] Poly(butylene succinate-co-butylene terephthalate), PBST for short, is another biodegradable fat-aromatic copolyester that has been industrially produced after poly(butylene adipate-co-butylene terephthalate), PBAT for short. Its thermal and mechanical properties are comparable to those of PBAT, and it has better gas barrier properties and transparency, making it more advantageous for use as packaging materials. However, the crystallinity of PBST is not as good as that of PBAT, especially under conditions of rapid cooling, PBST crystallizes slowly, which affects its melt processability and application. Although the gas barrier properties and transparency of PBST are better than those of PBAT, compared with other commonly used packaging materials, their gas barrier properties and transparency are still relatively low and need to be further improved. Therefore, crystallization modification of PBST is an urgent need for the promotion and application of PBST, and its gas barrier properties and transparency also need to be further improved.
[0003] The most commonly used polymer crystallization promotion technology is to add a nucleating agent to the polymer, which can increase the crystallization temperature and crystallization speed by directly or inducing the increase in the number of crystal nuclei. At present, a variety of nucleating agents that can be used for crystallization modification of PBST and PBAT copolyesters have been disclosed. For example, CN102558521A discloses a polyfumaric acid diol ester and its copolyester nucleating agent, and its 1wt% dosage can respectively The melt crystallization temperature of PBST at a cooling rate of 10°C / min was increased to 77.8°C and 73.4°C, an increase of 5.3°C and 10.9°C, but the data of melt crystallization enthalpy were not reflected; CN108384200A discloses a melamine / cyanuric acid complex nucleating agent, the dosage of which 1wt% and 5wt% can increase the melt crystallization temperature of PBAT at a cooling rate of 10°C / min by 15.6°C and 21.7°C, respectively, and the final crystallization temperatures are 68.2°C and 74.2°C, respectively, and the melt crystallization enthalpies are 17.1J / g and 16.8J / g, respectively. ; CN102492248A discloses the technology of using polyvinyl acetal as a nucleating agent, and its 1wt% dosage can increase the melt crystallization temperature of PBAT at a cooling rate of 10℃ / min to 81.4℃, which is 6.8℃ higher, but no melt crystallization enthalpy data is given; CN111100272A, CN111100427A, and CN111100270A disclose the technology of using similar copolyester oligomers and aromatic polyester oligomers with high aromatic chain content as nucleating agents for aliphatic-aromatic copolyesters, but no differential scanning calorimetry (DSC) data is provided. Although the above nucleating agents have a certain crystallization promoting effect on aliphatic-aromatic copolyesters at a conventional DSC cooling rate (10℃ / min), they often have poor effects under the actual processing conditions of rapid cooling (cooling rate often reaches tens of degrees Celsius per minute), and some nucleating agents are not biodegradable. The above-mentioned publications also do not provide the effect of nucleating agents on the gas barrier properties and transparency of aliphatic-aromatic copolyesters.
[0004] In summary, developing a fat-aromatic copolyester material that can still crystallize quickly under actual processing conditions of rapid cooling and can improve gas barrier properties and transparency is still a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems in the prior art that the gas barrier properties and transparency of fat-aromatic copolyester materials need to be improved and the crystallization effect under rapid cooling conditions is poor, and to provide a fat-aromatic copolyester material and a preparation method and application thereof. The fat-aromatic copolyester material has a fast crystallization rate under rapid cooling conditions, and while maintaining the original properties of the copolyester, the gas barrier properties and transparency are significantly improved.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a fat-aromatic copolyester material, wherein the melt crystallization temperature of the fat-aromatic copolyester material at a cooling rate of 40°C / min is 51-60°C, and the melt crystallization enthalpy is 8-22J / g, and the melt crystallization temperature at a cooling rate of 10°C / min is 65-90°C, and the melt crystallization enthalpy is 19-23J / g.
[0007] The second aspect of the present invention provides a method for preparing a fat-aromatic copolyester material, the method comprising the following steps: melt-mixing a fat-aromatic copolyester I with a nucleating agent; the nucleating agent is a precipitate obtained by precipitation treatment of a fat-aromatic copolyester II, the weight of the fat-aromatic copolyester I is greater than the weight of the nucleating agent; the fat-aromatic copolyester I contains a structural unit A represented by formula (III) and a structural unit B represented by formula (IV), the fat-aromatic copolyester II contains a structural unit C represented by formula (V) and a structural unit D represented by formula (VI), the molar percentage of the structural unit A in the fat-aromatic copolyester I is less than the molar percentage of the structural unit C in the fat-aromatic copolyester II;
[0008]
[0009] Wherein, the R1 and R4 are each independently a phenylene group and / or a phenylene group containing 1-2 C1-C4 alkyl substituents, the R2 and R5 are each independently a C2-C6 alkylene group, the R3 is a C0-C4 alkylene group, and the R6 is a C0-C2 alkylene group.
[0010] The third aspect of the present invention provides the use of the above-mentioned fat-aromatic copolyester material and / or the fat-aromatic copolyester material prepared by the above-mentioned method in packaging materials and / or ground films.
[0011] Through the above technical solution, the beneficial effects of the present invention are:
[0012] The fat-aromatic copolyester material provided by the present invention has a higher melt crystallization temperature and a higher melt crystallization enthalpy under a cooling rate of 40°C / min, can be crystallized faster under a fast cooling condition in actual processing, and the processability of the copolyester material melt is improved. At the same time, the copolyester material can also be crystallized quickly under conventional DSC cooling conditions (10°C / min), so that the copolyester material not only has good gas barrier properties, but also the formed copolyester film has high light transmittance and low haze, which is conducive to promoting the promotion and application of the copolyester material in the fields of packaging materials, ground films, etc.
[0013] The fat-aromatic copolyester material provided by the present invention uses fat-aromatic copolyester I as a matrix and a precipitate of fat-aromatic copolyester II as a nucleating agent during the preparation process, so that the nucleating agent has a significantly better crystallization promoting effect, and has a chemical structure and crystal structure similar to the matrix polyester, and the two have good compatibility. The nucleating agent is easily and evenly dispersed in the matrix polyester, which helps it to fully play its role in promoting the crystallization of the matrix, so that the copolyester material can be crystallized faster under the condition of rapid cooling in actual processing, and has better crystallinity; and the nucleating agent does not have an adverse effect on the transparency of the material. Further, the fat-aromatic copolyester I is biodegradable, and the nucleating agent is also a fat-aromatic copolyester II with good biodegradability, so that the copolyester material can maintain excellent biodegradability.
[0014] The preparation method of the fat-aromatic copolyester material provided by the invention can be prepared by using conventional plastic processing methods and equipment, the method is simple and feasible, and is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 PBST 44 PBST 48 and PBAT 48 DSC results are compared; A is the first heating curve, B is the cooling curve (10℃ / min), and C is the second heating curve. Under the corresponding rapid cooling conditions, a is the first heating curve, b is the cooling curve (40℃ / min), and c is the second heating curve.
[0016] Figure 2 Examples 1-5, Comparative Examples 1-4 and PBST 44 PBST 48 PBAT 48 DSC primary heating curve during normal cooling rate (10℃ / min) test;
[0017] Figure 3 Examples 1-5, Comparative Examples 1-4 and PBST 44 PBST 48 PBAT 48 DSC primary heating curve during the rapid cooling rate (40℃ / min) test;
[0018] Figure 4 Examples 1-5, Comparative Examples 1-4 and PBST 44 PBST 48 PBAT 48 DSC cooling curve during normal cooling rate (10℃ / min) test;
[0019] Figure 5Examples 1-5, Comparative Examples 1-4 and PBST 44 PBST 48 PBAT 48 DSC cooling curve during the fast cooling rate (40℃ / min) test;
[0020] Figure 6 Examples 1-5, Comparative Examples 1-4 and PBST 44 PBST 48 PBAT 48 DSC secondary heating curve during normal cooling rate (10℃ / min) test;
[0021] Figure 7 Examples 1-5, Comparative Examples 1-4 and PBST 44 PBST 48 PBAT 48 DSC secondary heating curve during the rapid cooling rate (40℃ / min) test;
[0022] Figure 8 PBST 44 (left, thickness 330 μm) and the transparency comparison of the aliphatic-aromatic copolyester material prepared in Example 2 (right, thickness 360 μm);
[0023] Fig. 9 PBST 44 (left, thickness is 330 μm) and the transparency comparison of the aliphatic-aromatic copolyester material prepared in Example 2 (right, thickness is 360 μm). DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] The first aspect of the present invention provides a fat-aromatic copolyester material, wherein the melt crystallization temperature of the fat-aromatic copolyester material at a cooling rate of 40°C / min is 51-60°C, and the melt crystallization enthalpy is 8-22J / g, and the melt crystallization temperature at a cooling rate of 10°C / min is 65-90°C, and the melt crystallization enthalpy is 19-23J / g.
[0026] The fat-aromatic copolyester material provided by the present invention has a high melt crystallization temperature and a high melt crystallization enthalpy under a rapid cooling condition (40°C / min), and can be crystallized relatively quickly under a rapid cooling condition in actual processing, thereby improving the processability of the copolyester material melt; the fat-aromatic copolyester material also has good crystallization performance under conventional cooling conditions, and can also be crystallized rapidly under a DSC cooling condition of 10°C / min. The performance of the fat-aromatic copolyester material is conducive to improving the light transmission performance of the copolyester material, and promoting the promotion and application of the copolyester material in the fields of packaging materials, ground films, etc.
[0027] According to the present invention, preferably, the melt crystallization temperature of the aliphatic-aromatic copolyester material at a cooling rate of 40°C / min is 55-60°C, and the melt crystallization enthalpy is 19-22 J / g; the melt crystallization temperature at a cooling rate of 10°C / min is 80-87°C. At this time, the copolyester material has more excellent crystallinity under rapid cooling conditions, and the formed film has higher light transmittance and lower haze.
[0028] In the present invention, the melt crystallization temperature, melt crystallization enthalpy, melting enthalpy and other thermal transition properties of the aliphatic-aromatic copolyester material at a cooling rate of 40°C / min or 10°C / min are tested by a differential scanning calorimeter (DSC, for example, model TAInstrument Q200), using a standard test procedure of "heating-cooling-heating", with a heating rate of 10°C / min, heating to 220°C and keeping the temperature for 5 minutes, and cooling at a rate of 40°C / min or 10°C / min.
[0029] The fat-aromatic copolyester material provided by the present invention has significantly improved gas barrier properties and transparency based on the optimization of its crystallization performance under rapid cooling. Preferably, the oxygen permeability coefficient of the fat-aromatic copolyester material is 0.23-0.29 barrer, and the carbon dioxide permeability coefficient is 2.6-3 barrer; when the thickness of the fat-aromatic copolyester material is 380-420 μm, the light transmittance is 51-75%, more preferably 70-75%; the haze is 25-90%, more preferably 25-40%.
[0030] The gas barrier properties (oxygen and carbon dioxide gas permeability coefficients) of the aliphatic-aromatic copolyester material are tested by a gas permeameter (e.g., model Labstone Instruments Technology BSG-33E), and the water vapor permeability is tested by a constant temperature and humidity chamber. The test film is made by a hot pressing method, and the film thickness is 300-400 μm. At least 3 groups of data are measured for each sample and the average is calculated. The gas permeability (GTR) is measured by a pressure difference method at 23° C. and 0 RH% with the help of a gas permeameter. The gas permeability coefficient P (=GTR×d / ΔP) can be calculated based on the GTR, film thickness (d), and pressure difference (ΔP) on both sides of the film.
[0031] The transparency indexes of the aliphatic-aromatic copolyester material in the visible light wavelength range, namely, transmittance and haze, are measured by a spectrophotometer (e.g., model CS-821N manufactured by Hangzhou Color Spectrum Technology Co., Ltd.). The film used for the test is prepared by hot pressing, and the film thickness is 400±20 μm.
[0032] According to the present invention, preferably, the aliphatic-aromatic copolyester material contains a structural unit a represented by formula (I) and a structural unit b represented by formula (II),
[0033]
[0034] Among them, the R I is phenylene and / or phenylene containing 1-2 C1-C4 alkyl substituents, R I When it is a phenylene group, the adjacent carbonyl group may be located at the ortho, meta or para position on the phenylene group; R I When it is a phenylene group containing 1-2 C1-C4 alkyl substituents, the adjacent carbonyl group may be located at the ortho, meta or para position on the phenylene group, or may be connected to the alkyl substituent on the phenylene group. II is a C2-C6 alkylene group, for example, an ethylene group, a straight-chain or branched propylene group, a straight-chain or branched butylene group, a straight-chain or branched pentylene group, or a straight-chain or branched hexylene group; III It is a C0-C4 alkylene group, for example, it can be C0, methylene, ethylene, a straight-chain or branched-chain propylene group, or a straight-chain or branched-chain butylene group.
[0035] According to the present invention, preferably, the molar percentage of the structural unit a in the aliphatic-aromatic copolyester material is 43.5-49 mol%, more preferably 44.8-49 mol%. Under this preferred embodiment, it is beneficial for the aliphatic-aromatic copolyester material to have a higher melt crystallization temperature and a higher melt crystallization enthalpy, and further improve the processability of the copolyester material melt. Wherein, the molar percentage of the structural unit a refers to the percentage of the molar amount of the structural unit a to the sum of the molar amounts of all repeating ester units in the aliphatic-aromatic copolyester material.
[0036] The second aspect of the present invention provides a method for preparing a fat-aromatic copolyester material, the method comprising the following steps: melt-mixing a fat-aromatic copolyester I with a nucleating agent; the nucleating agent is a precipitate obtained by precipitation treatment of a fat-aromatic copolyester II, the weight of the fat-aromatic copolyester I is greater than the weight of the nucleating agent; the fat-aromatic copolyester I contains a structural unit A represented by formula (III) and a structural unit B represented by formula (IV), the fat-aromatic copolyester II contains a structural unit C represented by formula (V) and a structural unit D represented by formula (VI), the molar percentage of the structural unit A in the fat-aromatic copolyester I is less than the molar percentage of the structural unit C in the fat-aromatic copolyester II;
[0037]
[0038] Wherein, the R1 and R4 are each independently a phenylene group and / or a phenylene group containing 1-2 C1-C4 alkyl substituents. When R1 and / or R4 are phenylene groups, the adjacent carbonyl groups may be located at the ortho, meta or para positions on the phenylene group; when R1 and / or R4 are phenylene groups containing 1-2 C1-C4 alkyl substituents, the adjacent carbonyl groups may be located at the ortho, meta or para positions on the phenylene group, or may be connected to the alkyl substituents on the phenylene group. The R2 and R5 are each independently a C2-C6 alkylene group, for example, an ethylene group, a straight or branched propylene group, a straight or branched butylene group, a straight or branched pentylene group, or a straight or branched hexylene group; the R3 is a C0-C4 alkylene group, for example, a C0, a methylene group, an ethylene group, a straight or branched propylene group, or a straight or branched butylene group; the R6 is a C0-C2 alkylene group, for example, a C0, a methylene group, or an ethylene group.
[0039] In the present invention, the molar percentage of structural unit A in aliphatic-aromatic copolyester I refers to the percentage of the molar amount of structural unit A to the sum of the molar amounts of all repeating ester units in aliphatic-aromatic copolyester I, and the molar percentage of structural unit C in aliphatic-aromatic copolyester II refers to the percentage of the molar amount of structural unit C to the sum of the molar amounts of all repeating ester units in aliphatic-aromatic copolyester II.
[0040] The fat-aromatic copolyester material provided by the present invention uses a fat-aromatic copolyester I with a low content of structural unit A (belonging to aromatic diacid ester units) as a matrix, and uses a precipitate obtained from a fat-aromatic copolyester II with a high content of structural unit C (also belonging to aromatic diacid ester units) as a nucleating agent during the preparation process, so that the nucleating agent has a significantly better crystallization promotion effect, and has a chemical structure and crystal structure similar to those of the matrix polyester (due to the similar chemical structure, the nucleating agent can be called a self-nucleating agent), can effectively promote the crystallization of the matrix polyester, can not only quickly crystallize under a conventional DSC cooling rate, but also can realize that the copolyester material can be crystallized faster under the condition of rapid cooling in actual processing, has better crystallinity, and at the same time, the gas barrier property and transparency are also significantly improved; the matrix and the nucleating agent have good compatibility, and the nucleating agent is easy to be evenly dispersed in the matrix polyester, which helps it to fully play its role in promoting the crystallization of the matrix.
[0041] According to the present invention, preferably, the amount of the aliphatic-aromatic copolyester I accounts for 95wt%-99.7wt% of the total amount of the aliphatic-aromatic copolyester I and the nucleating agent, preferably 97wt%-99.5wt%. The inventors found that under this preferred embodiment, it is beneficial to improve the crystallization stability of the prepared copolyester material, and make the material have good gas barrier properties and transparency.
[0042] According to the present invention, under the premise that the molar percentage of structural unit A in the fat-aromatic copolyester I is less than the molar percentage of structural unit C in the fat-aromatic copolyester II, preferably, the molar percentage of structural unit A in the fat-aromatic copolyester I is 43-55 mol%, more preferably 44-48 mol%; the molar percentage of structural unit C in the fat-aromatic copolyester II is 55-80 mol%, more preferably 61-71 mol%. The inventors found that under this preferred embodiment, the precipitate of the fat-aromatic copolyester II is conducive to better promoting the crystallization of the fat-aromatic copolyester I, thereby improving the crystallization performance of the copolyester material.
[0043] According to the present invention, R1 and R4 may be the same or different; R2 and R5 may be the same or different; and R3 and R6 may be the same or different. Preferably, R1 and R4 are the same, R2 and R5 are the same, and R3 and R6 are also the same. The difference between the aliphatic-aromatic copolyester I and the aliphatic-aromatic copolyester II is that the molar percentages of the corresponding aromatic diacid ester units (structural unit A and structural unit C) are different.
[0044] According to the present invention, preferably, R1 and R4 are each independently a phenylene group, and more preferably, the adjacent carbonyl group is located at the para position on the phenylene group; R2 and R5 are each independently a butylene group, and more preferably a straight-chain butylene group; R3 is an ethylene group and / or a butylene group, and more preferably an ethylene group or a straight-chain butylene group; and R6 is an ethylene group.
[0045] According to the present invention, the structural unit B is formed by esterifying a dibasic acid or ester derivative containing an R3 group with a diol containing an R2 group, the structural unit A is formed by esterifying a dibasic acid or ester derivative containing an R1 group with a diol containing an R2 group; the structural unit D is formed by esterifying a dibasic acid or ester derivative containing an R6 group with a diol containing an R5 group, and the structural unit C is formed by esterifying a dibasic acid or ester derivative containing an R4 group with a diol containing an R5 group. That is, the aliphatic-aromatic copolyester I can be obtained by co-polycondensation reaction of a dibasic acid or ester derivative containing an R1 group, a dibasic acid or ester derivative containing an R3 group, and a diol containing an R2 group, and the molar amount of each monomer is adjusted so that the structural unit A in the aliphatic-aromatic copolyester I is the desired molar percentage; the aliphatic-aromatic copolyester II can be obtained by co-polycondensation reaction of a dibasic acid or ester derivative containing an R4 group, a dibasic acid or ester derivative containing an R6 group, and a diol containing an R5 group, and the molar amount of each monomer is adjusted so that the structural unit C in the aliphatic-aromatic copolyester II is the desired molar percentage. In the present invention, the conditions of the co-polycondensation reaction can be in accordance with the conventional co-polycondensation reaction conditions in the prior art.
[0046] According to the present invention, preferably, the dibasic acid or ester derivative containing an R1 group and the dibasic acid or ester derivative containing an R4 group are each independently selected from one or more of terephthalic acid, dimethyl terephthalate, isophthalic acid and dimethyl isophthalate, and terephthalic acid is further preferred; the dihydric alcohol containing an R2 group and the dihydric alcohol containing an R5 group are each independently selected from one or more of 1,4-butanediol, 1,3-butanediol and 1,2-butanediol, and 1,4-butanediol is further preferred; the dibasic acid containing an R3 group Or ester derivatives and dibasic acid or ester derivatives containing R6 groups are each independently selected from one or more of 1,4-butanedioic acid, 1,4-dimethyl butanedioate, 1,3-butanedioic acid, 1,2-butanedioic acid, 1,6-hexanedioic acid, 1,6-dimethyl hexanedioate, 1,2-hexanedioic acid, 1,3-hexanedioic acid, 1,4-hexanedioic acid, and 1,5-hexanedioic acid. Further preferably, the dibasic acid or ester derivative containing R3 groups is 1,4-butanedioic acid or 1,6-hexanedioic acid, and the dibasic acid or ester derivative containing R6 groups is 1,4-butanedioic acid.
[0047] The above substances in the present invention are conventionally selected in the art and can be obtained commercially.
[0048] For example, the aliphatic-aromatic copolyester I and the aliphatic-aromatic copolyester II in the present invention both use poly(butylene succinate-co-butylene terephthalate), referred to as PBST. Since the aliphatic-aromatic copolyester II itself has good biodegradability and is used in a small amount, the aliphatic-aromatic copolyester material can have excellent biodegradability. At this time, the copolymer composition of PBST is represented by the molar percentage Xmol% of the aromatic diacid ester unit (butylene terephthalate, abbreviated as BT) structural unit, and it is recorded as PBST x For example, PBST 48 The molar amount of BT structural unit in the PBST is 48 mol% of the total molar amount of BT structural unit and butylene succinate structural unit. It is prepared by melt polycondensation of terephthalic acid, 1,4-butanediol and 1,4-butanediol, and has an intrinsic viscosity of 1.01 dL / g. 71 The molar amount of the BT structural unit in the terephthalic acid ester structural unit accounts for 71 mol% of the total molar amount of the BT structural unit and the butylene succinate structural unit. It is prepared by melt polycondensation of terephthalic acid, 1,4-butanediol and 1,4-butanediol, and has an intrinsic viscosity of 0.77 dL / g.
[0049] According to the present invention, preferably, the precipitation treatment process comprises: contacting the fat-aromatic copolyester II with a precipitant in the presence of a solvent; further preferably, the contact process comprises: mixing and dissolving the fat-aromatic copolyester II with the solvent, and then mixing and precipitating with the precipitant. The precipitation treatment process can be carried out at room temperature (25±5°C) and air atmosphere, and the solvent can be recycled. The inventors have found that under this preferred embodiment, it is beneficial to improve the precipitation effect on the fat-aromatic copolyester II, thereby enhancing the crystallization promotion effect on the fat-aromatic copolyester I.
[0050] According to the present invention, preferably, the solvent is selected from one or more of dichloromethane, chloroform and a phenol-tetrachloroethane mixture, wherein the phenol-tetrachloroethane mixture preferably has a volume ratio of phenol to tetrachloroethane of 1-1.5: 1. More preferably, the solvent is chloroform.
[0051] According to the present invention, preferably, the precipitant is selected from one or more of aliphatic alcohols, aliphatic ketones and water, more preferably selected from one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, acetone and water, and further preferably methanol and / or ethanol. By combining the solvent and the precipitant, the precipitation effect on the aliphatic-aromatic copolyester II can be better achieved.
[0052] In the present invention, the precipitation treatment process further comprises: performing solid-liquid separation on the solution obtained by mixed precipitation to obtain a precipitate, and washing and drying the precipitate and then using it as a nucleating agent.
[0053] According to the present invention, in order to better achieve the mixing effect of the aliphatic-aromatic copolyester I and the nucleating agent, preferably, the melt mixing conditions at least include: a temperature of 150-250° C. and a time of 4-10 min.
[0054] In the present invention, the processes such as melt mixing can be carried out in conventional processing equipment, such as a stirring kettle, a twin-screw extruder, a single-screw extruder or an internal mixer, which is easy to operate and convenient for industrial production.
[0055] The third aspect of the present invention provides the use of the above-mentioned fat-aromatic copolyester material and / or the fat-aromatic copolyester material prepared by the above-mentioned method in packaging materials and / or ground films.
[0056] According to a particularly preferred embodiment of the present invention, the method for preparing the aliphatic-aromatic copolyester material comprises the following steps:
[0057] (1) mixing and dissolving aliphatic-aromatic copolyester II with a solvent, and then mixing and precipitating with a precipitant to obtain a precipitate, performing solid-liquid separation on the precipitate to obtain a precipitate, and washing and drying the precipitate as a nucleating agent;
[0058] (2) mixing the nucleating agent and the aliphatic-aromatic copolyester I at a temperature of 150-250° C. for 4-10 minutes;
[0059] Wherein, the amount of the aliphatic-aromatic copolyester I accounts for 95wt%-99.7wt% of the total amount of the aliphatic-aromatic copolyester I and the nucleating agent;
[0060] The aliphatic-aromatic copolyester I contains a structural unit A represented by formula (III) and a structural unit B represented by formula (IV); the aliphatic-aromatic copolyester II contains a structural unit C represented by formula (V) and a structural unit D represented by formula (VI); the molar percentage of the structural unit C in the aliphatic-aromatic copolyester II is 55-80 mol%, and the molar percentage of the structural unit A in the aliphatic-aromatic copolyester I is 43-55 mol% and is less than the molar percentage of the structural unit C in the aliphatic-aromatic copolyester II; the R1 and R4 are each independently a phenylene group and the adjacent carbonyl group is located at the para position on the phenylene group; the R2 and R5 are each independently a straight-chain butylene group; the R3 is an ethylene group or a straight-chain butylene group; and the R6 is an ethylene group.
[0061] The present invention will be described in detail below through examples.
[0062] In the following examples, the names and abbreviations of the copolyesters used are as follows: poly(butylene succinate-co-butylene terephthalate), abbreviated as PBST; poly(butylene adipate-co-butylene terephthalate), abbreviated as PBAT; the copolymer composition of PBST or PBAT is represented by the molar percentage x mol% of the aromatic diacid unit (butylene terephthalate, abbreviated as BT) structural unit, and is recorded as PBST x Or PBAT x .
[0063] In the following examples, PBST 44 PBAT 48 PBST 61 All provided by Sinopec Yizheng Chemical Fiber Co., Ltd., PBST 48 It is made by melt polycondensation of terephthalic acid, 1,4-butanediol and 1,4-butanediol, with an intrinsic viscosity of 1.01dL / g; PBST 71 It is prepared by melt polycondensation of terephthalic acid, 1,4-butanediol and 1,4-butanediol. The molar percentage of BT chain segments is 71 mol%, and the intrinsic viscosity is 0.77 dL / g. It should be noted that PBST 44 The mass fraction of BT chain segments is 50.1wt%, which is comparable to PBAT. 48 The BT chain mass fraction (50.4wt%) is equivalent.
[0064] When PBST is used for aliphatic-aromatic copolyester I, it is referred to as PBST x When PBST is used for the aliphatic-aromatic copolyester II, it is recorded as PBST y The precipitate of aliphatic-aromatic copolyester II is recorded as sPBST y When the aliphatic-aromatic copolyester II is used as the nucleating agent, the mass percentages of the aliphatic-aromatic copolyester I and the nucleating agent are a wt% and b wt% (a+b=100), respectively, so it is named x a y b Similarly, when the precipitate of aliphatic-aromatic copolyester II is used as a nucleating agent, it is named x a sy b ; When aliphatic-aromatic copolyester I and aliphatic-aromatic copolyester II use PBAT, the naming method is similar.
[0065] In the following examples, the composition of the aliphatic-aromatic copolyesters was determined by H-NMR spectroscopy;
[0066] The melting point, crystallization temperature, crystallization enthalpy, melting enthalpy and other thermal transition properties of the aliphatic-aromatic copolyester material were tested using a TAInstrument Q200 differential scanning calorimeter. The standard test procedure of "heating-cooling-heating" was adopted. The heating rate was 10°C / min, the temperature was raised to 220°C and kept for 5 minutes, and the temperature was cooled at a rate of 40°C / min or 10°C / min, respectively.
[0067] The gas barrier properties of the aliphatic-aromatic copolyester material, such as oxygen and carbon dioxide gas permeability coefficients, were tested using a Labstone Instruments Technology BSG-33E gas permeameter, and the water vapor permeability was tested using a constant temperature and humidity chamber; the test film was made by a hot pressing method, with a film thickness of 300-400 μm, and at least 3 groups of data were measured for each sample to obtain an average; the gas permeability (GTR) was measured by a pressure difference method at 23°C and 0RH% with the aid of a gas permeameter, and the gas permeability coefficient P (=GTR×d / ΔP) can be calculated based on the GTR, film thickness (d), and pressure difference (ΔP) on both sides of the film.
[0068] The transparency indexes of aliphatic-aromatic copolyester materials in the visible light wavelength range, namely transmittance and haze, were measured by CS-821N Hangzhou Color Spectrum benchtop spectrophotometer. The film used for the test was made by hot pressing method and had a film thickness of 400±20μm.
[0069] The molar percentages of structural unit a in the aliphatic-aromatic copolyester material, structural unit A in the aliphatic-aromatic copolyester I and structural unit C in the aliphatic-aromatic copolyester II were detected by nuclear magnetic hydrogen spectrum.
[0070] Example 1
[0071] (1) Mix 1 part (1 part is 1 g, the same below) of PBST 61 Dissolve in 30 parts of chloroform to obtain PBST 61 Solution, add methanol dropwise to PBST 61 The solution was stirred until no more precipitate was precipitated (methanol was used in an amount of about 60 parts) to obtain a solid-liquid mixture containing precipitate; the solid-liquid mixture was filtered to obtain a precipitate, and the precipitate was washed with ethanol and dried to obtain sPBST 61 as a nucleating agent;
[0072] (2) 1 g of sPBST 61 With 99g PBST 44 The mixture was melt-mixed in an internal mixer at 200°C for 5 min to obtain a fat-aromatic copolyester material, which was recorded as 44. 99 s611.
[0073] Example 2
[0074] (1) Mix 1 portion of PBST 61 Dissolve in 30 parts of chloroform to obtain PBST 61 Solution, add methanol dropwise to PBST 61 The solution was stirred until no more precipitate was precipitated (methanol was used in an amount of about 60 parts) to obtain a solid-liquid mixture containing precipitate; the solid-liquid mixture was filtered to obtain a precipitate, and the precipitate was washed with ethanol and dried to obtain sPBST 61 as a nucleating agent;
[0075] (2) 5 g of sPBST 61 With 95g PBST 44 The mixture was melt-mixed in an internal mixer at 240°C for 4 min to obtain a fat-aromatic copolyester material, which was recorded as 44 95 s615.
[0076] Example 3
[0077] (1) Mix 1 portion of PBST 71 Dissolve in 20 parts chloroform and 10 parts dichloromethane to obtain PBST 71 Solution, add ethanol dropwise to PBST 71 The solution was stirred until no more precipitate was precipitated (the amount of ethanol used was about 60 parts), to obtain a solid-liquid mixture containing precipitate; the solid-liquid mixture was filtered to obtain a precipitate, and the precipitate was washed with ethanol and dried to obtain sPBST 71 as a nucleating agent;
[0078] (2) 1 g of sPBST 71 With 99g PBST 44 The mixture was melt-mixed in an internal mixer at 220°C for 8 min to obtain a fat-aromatic copolyester material, which was recorded as 44. 99 s711.
[0079] Example 4
[0080] (1) Mix 1 portion of PBST 71 Dissolve in 30 parts of chloroform to obtain PBST 71 Solution, add ethanol dropwise to PBST 71 The solution was stirred until no more precipitate was precipitated (the amount of ethanol used was about 60 parts), to obtain a solid-liquid mixture containing precipitate; the solid-liquid mixture was filtered to obtain a precipitate, and the precipitate was washed with ethanol and dried to obtain sPBST 71 as a nucleating agent;
[0081] (2) 3 g of sPBST 71 With 97g PBST 44 The mixture was melt-mixed in an internal mixer at 200°C for 5 min to obtain a fat-aromatic copolyester material, which was recorded as 44. 97s713.
[0082] Example 5
[0083] The fat-aromatic copolyester material was prepared according to the method of Example 4, except that PBST 44 Replaced by PBST 48 , obtain a fat-aromatic copolyester material, recorded as 48 97 s713.
[0084] Comparative Example 1
[0085] 1 g PBST 61 With 99g PBST 44 The mixture was melt-mixed in an internal mixer at 200°C for 5 min to obtain a fat-aromatic copolyester material, which was recorded as 44. 99 611.
[0086] Comparative Example 2
[0087] 5 g PBST 61 With 95g PBST 44 The mixture was melt-mixed in an internal mixer at 200°C for 5 min to obtain a fat-aromatic copolyester material, which was recorded as 44. 95 615.
[0088] Comparative Example 3
[0089] 1 g PBST 71 With 99g PBST 44 The mixture was melt-mixed in an internal mixer at 200°C for 5 min to obtain a fat-aromatic copolyester material, which was recorded as 44. 99 711.
[0090] Comparative Example 4
[0091] 3 g PBST 71 With 97g PBST 44 The mixture was melt-mixed in an internal mixer at 200°C for 5 min to obtain a fat-aromatic copolyester material, which was recorded as 44. 97 713.
[0092] Comparative Examples 5-7
[0093] PBST 44 PBST 48 PBAT 48 They are respectively referred to as Comparative Examples 5-7.
[0094] Test Example 1
[0095] The fat-aromatic copolyester materials prepared in Examples 1 to 5 and the fat-aromatic copolyester materials prepared in Comparative Examples 1 to 4, PBST 44 PBST 48 PBAT 48 The DSC results are shown in Figure 1 , Figure 2-Figure 7 and Table 1; Testing Examples 1-5 prepared fat-aromatic copolyester materials and Comparative Examples 1-4 prepared fat-aromatic copolyester materials, PBST 44 PBST 48 PBAT 48 The content of structural unit a in the mixture is shown in Table 1.
[0096] Table 1
[0097]
[0098] Table 1 T c Indicates the melt crystallization temperature; ΔH c Indicates melt crystallization enthalpy; * indicates PBST at a cooling rate of 40℃ / min 48 There is no obvious melt crystallization peak. This value is the difference between the secondary heating melting enthalpy and the cold crystallization enthalpy. Theoretically, it is equal to the melt crystallization enthalpy, but the error is often large.
[0099] DSC results (Table 1 and Figure 1 ) shows that PBAT 48 It can crystallize quickly at both 10℃ / min and 40℃ / min cooling rates, but its melt crystallization temperature drops significantly at 40℃ / min. 48 Compared with PBST with the same BT chain mole percentage 48 At a cooling rate of 10°C / min, the melt crystallization temperature is 62°C, the melt crystallization enthalpy is 20.6J / g, and the crystallinity is not as good as PBAT. 48 Poor; however, it is difficult to observe a clear melt crystallization peak at a cooling rate of 40°C / min, and the crystallinity is obviously inferior to that of PBAT 48 . With PBAT 48 Compared with PBST with the same BT chain mass content 44 At a cooling rate of 10°C / min, the melt crystallization temperature dropped significantly to 21°C, and the melt crystallization enthalpy was 15.5J / g, and the crystallinity was far inferior to that of PBAT. 48 ; However, at a cooling rate of 40°C / min, no melt crystallization peak was observed, indicating that the crystallization ability was lost. The above results show that under the usual composition (BT molar percentage is 43-50mol%), PBST crystallizes slowly or even does not crystallize under rapid cooling conditions, thus making it difficult to meet the requirements of processing and application.
[0100] Comparative Examples 1 to 4 use PBST (PBST 61 PBST 71 ) as a nucleating agent for PBST 44 Crystallization modification was performed, and 1wt% and 5wt% PBST were added at a cooling rate of 10℃ / min. 61 PBST 44 The crystallization temperature of PBST increased from 21℃ to 62℃ and 72℃, and the melt crystallization enthalpy increased from 15.5J / g to 20.5J / g and 19.1J / g, respectively; 1wt% and 3wt% PBST 71 PBST 44 The crystallization temperature of PBST increased from 21℃ to 69℃ and 79℃ respectively, and the melt crystallization enthalpy increased from 15.5J / g to 19.7J / g and 18.9J / g respectively, and the crystallization promoting effect was quite obvious. However, in the actual melt processing, the cooling rate of PBST is much faster than 10℃ / min. Therefore, the DSC results under the condition of rapid cooling can better illustrate the real effect of the nucleating agent. Under the DSC cooling rate of 40℃ / min, under the condition of PBST 44 1wt% and 5wt% PBST were introduced into 61 , the obtained compositions showed melt crystallization, the melt crystallization temperatures were 42℃ and 47℃, and the melt crystallization enthalpies were increased to 6.3J / g and 12.5J / g, respectively; 44 1wt% and 3wt% PBST were introduced into 71 The melt crystallization temperatures of the obtained compositions were 48°C and 50°C, and the melt crystallization enthalpies were 9.8 J / g and 15.5 J / g, respectively. It can be seen that the use of PBST with a high BT chain content as a self-nucleating agent for PBST matrix resin has obvious effects under slow cooling conditions, and the melt crystallization temperature and crystallization enthalpy are significantly improved. Under fast cooling conditions, it can also form a certain crystallization promotion effect.
[0101] See also Figure 2-Figure 7 Table 1, Example 1-Example 5 with sPBST after dissolution and precipitation 61 sPBST 71 Mixed into PBST as a self-nucleating agent 44 PBST 48 The obtained PBST composition has significantly better crystallinity in the matrix resin. Under the condition of slow cooling at 10℃ / min, 1wt% and 5wt% sPBST were introduced. 61 , the resulting PBST 44 The crystallization temperature of the composition is from PBST 44The 21 wt% and 3 wt% sPBST were introduced into the 71 , the resulting PBST 44 The crystallization temperature of the composition is from PBST 44 The 21℃ of the solution was increased to 72℃ and 87℃ respectively, and the melt crystallization enthalpy was increased to 20.1J / g and 19.3J / g respectively. The crystallization promoting effect was better than that of PBST which was not dissolved and precipitated. 61 PBST 71 As a self-nucleating agent. Under the condition of rapid cooling at 40℃ / min, 1wt% and 5wt% sPBST were introduced 61 , the resulting PBST 44 The melt crystallization temperature of the composition is 51°C and 52°C, and the melt crystallization enthalpy is 8.4 J / g and 15.7 J / g; 1 wt% and 3 wt% of sPBST are introduced 71 , the obtained PBST 44 The melt crystallization temperature of the composition is 53°C and 58°C, and the melt crystallization enthalpy is 13.1 J / g and 19.1 J / g. Although its crystallinity is not as good as the result under the slow cooling condition of 10°C / min, compared with the results of Comparative Examples 1 to 4 under the fast cooling condition, its melt crystallization temperature and melt crystallization enthalpy are significantly higher, showing a significantly better crystallization promoting effect.
[0102] See Example 5 for PBST 48 Matrix, introducing 3wt% sPBST 71 The obtained aliphatic-aromatic copolyester material has a crystallization temperature from PBST to 48 The temperature of the melt was increased from 62℃ to 86℃, and the melt crystallization enthalpy was increased from 20.6J / g to 22.1J / g; even under the condition of rapid cooling at 40℃ / min, the PBST with less obvious crystallization peak than the melt 48 Introduce 3wt% sPBST 71 The crystallization temperature of the obtained fat-aromatic copolyester material was increased to 60°C, and the melt crystallization enthalpy was increased from 8.8J / g to 21.3J / g, and the crystallization promoting effect was still very significant.
[0103] Therefore, in the rapid cooling process that is closer to actual production and processing, the fat-aromatic copolyester material provided by the present invention has more outstanding crystallization performance than the comparative example, showing a higher melt crystallization temperature and a higher melt crystallization enthalpy.
[0104] Test Example 2
[0105] The fat-aromatic copolyester materials prepared in Examples 1 to 5 and the fat-aromatic copolyester materials prepared in Comparative Examples 1 to 4, PBST 44 PBST 48 PBAT 48 The results of oxygen and carbon dioxide gas permeability coefficients, light transmittance and haze tests are shown in Table 2 and Figure 8 , Fig. 9 .
[0106] Table 2
[0107]
[0108] Table 2 P O2 is the oxygen permeability coefficient; P CO2 is the carbon dioxide permeability coefficient; 1barrer = 10 -10 cm 3 cm / (cm 2 ·s·cmHg); the thickness of the film used in the test is 400±20μm.
[0109] As shown in Table 2, compared with PBST 44 , introducing 1wt% and 5wt% sPBST 61 The oxygen permeability coefficients of the obtained aliphatic-aromatic copolyester materials decreased by 10% and 26%, respectively, and the carbon dioxide permeability coefficients decreased by 14% and 24%, respectively; compared with PBST 44 , introducing 1wt% and 3wt% sPBST 71 The oxygen permeability coefficients of the obtained aliphatic-aromatic copolyester materials decreased by 6% and 16%, respectively, and the carbon dioxide permeability coefficients decreased by 16% and 22%, respectively. 48 , introducing 3wt% sPBST 71 The oxygen and carbon dioxide permeability coefficients of the obtained aliphatic-aromatic copolyester material decreased by 14% and 4% respectively. It can be seen that the crystallization performance of the aliphatic-aromatic copolyester material prepared by the preparation method provided by the present invention is significantly improved, and the gas barrier property is also significantly improved accordingly.
[0110] The self-nucleating agent in the fat-aromatic copolyester material provided by the present invention has a similar chemical structure to the base polyester, and the two have good compatibility, which can avoid the decrease in transparency caused by microphase separation due to the addition of a heterogeneous nucleating agent; the excellent nucleating effect of the nucleating agent increases the number of crystals and reduces the size of the crystals, which improves the crystallization performance of the copolyester product and is more conducive to the transmission of visible light, so that the products made from the fat-aromatic copolyester material have better light transmittance; Figure 8 , Fig. 9 As shown in Table 2, its transmittance and haze are significantly better than those of PBST. 44 PBST48 The film made of matrix resin is better than PBAT 48 Film made of resin.
[0111] Therefore, the fat-aromatic copolyester material provided by the present invention has better crystallinity than the PBST matrix resin, and also has higher gas barrier properties and transparency than the PBST matrix resin, which is very important for the application of PBST in the fields of packaging materials, ground films, etc.
[0112] The self-nucleating agent used in the present invention is a sPBST resin with a BT molar percentage of 55-80 mol% and subjected to a dissolution-precipitation treatment, which still has certain biodegradability and is added in a small amount. Therefore, the fat-aromatic copolyester material prepared by melt blending the sPBST resin with a BT molar percentage of 43-55 mol% and the sPBST resin still has excellent biodegradability.
[0113] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A fatty-aromatic copolyester material, characterized in that: The melt crystallization temperature of the fat-aromatic copolyester material is 51-60°C and the melt crystallization enthalpy is 8-22 J / g at a cooling rate of 40°C / min, and the melt crystallization temperature is 65-90°C and the melt crystallization enthalpy is 19-23 J / g at a cooling rate of 10°C / min.
2. The aliphatic-aromatic copolyester material according to claim 1, characterized in that: The melt crystallization temperature of the aliphatic-aromatic copolyester material at a cooling rate of 40°C / min is 55-60°C, and the melt crystallization enthalpy is 19-22 J / g; Preferably, the melt crystallization temperature of the aliphatic-aromatic copolyester material at a cooling rate of 10°C / min is 80-87°C.
3. The aliphatic-aromatic copolyester material according to claim 1 or 2, characterized in that: The oxygen permeability coefficient of the aliphatic-aromatic copolyester material is 0.23-0.29 barrer, and the carbon dioxide permeability coefficient is 2.6-3 barrer; Preferably, when the thickness of the aliphatic-aromatic copolyester material is 380-420 μm, the light transmittance is 51-75%, more preferably 70-75%; the haze is 25-90%, more preferably 25-40%.
4. The aliphatic-aromatic copolyester material according to claim 1 or 2, characterized in that: The aliphatic-aromatic copolyester material contains a structural unit a represented by formula (I) and a structural unit b represented by formula (II), Among them, the R I is phenylene and / or phenylene containing 1-2 C1-C4 alkyl substituents, wherein R II is C2-C6 alkylene, said R III is C0-C4 alkylene; Preferably, the molar percentage of the structural unit a in the aliphatic-aromatic copolyester material is 43.5-49 mol%, more preferably 44.8-49 mol%.
5. A method for preparing a fat-aromatic copolyester material, characterized in that: The method comprises the following steps: melt-mixing aliphatic-aromatic copolyester I and a nucleating agent; The nucleating agent is a precipitate obtained by precipitation treatment of aliphatic-aromatic copolyester II, and the weight of the aliphatic-aromatic copolyester I is greater than the weight of the nucleating agent; The aliphatic-aromatic copolyester I contains a structural unit A represented by formula (III) and a structural unit B represented by formula (IV), and the aliphatic-aromatic copolyester II contains a structural unit C represented by formula (V) and a structural unit D represented by formula (VI), and the molar percentage of the structural unit A in the aliphatic-aromatic copolyester I is less than the molar percentage of the structural unit C in the aliphatic-aromatic copolyester II; Wherein, the R1 and R4 are each independently a phenylene group and / or a phenylene group containing 1-2 C1-C4 alkyl substituents, the R2 and R5 are each independently a C2-C6 alkylene group, the R3 is a C0-C4 alkylene group, and the R6 is a C0-C2 alkylene group.
6. The method according to claim 5, characterized in that The amount of the aliphatic-aromatic copolyester I accounts for 95wt%-99.7wt% of the total amount of the aliphatic-aromatic copolyester I and the nucleating agent, preferably 97wt%-99.5wt%; Preferably, R1 and R4 are each independently a phenylene group, R2 and R5 are each independently a butylene group, R3 is an ethylene group and / or a butylene group, and R6 is an ethylene group.
7. The method according to claim 5 or 6, characterized in that: The molar percentage of the structural unit A in the aliphatic-aromatic copolyester I is 43-55 mol%, preferably 44-48 mol%; Preferably, the molar percentage of the structural unit C in the aliphatic-aromatic copolyester II is 55-80 mol %, more preferably 61-71 mol %.
8. The method according to claim 5 or 6, characterized in that: The precipitation treatment process comprises: contacting the aliphatic-aromatic copolyester II with a precipitant in the presence of a solvent; Preferably, the solvent is selected from one or more of dichloromethane, chloroform and a phenol-tetrachloroethane mixture, more preferably chloroform; Preferably, the precipitant is selected from one or more of fatty alcohols, fatty ketones and water, more preferably selected from one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, acetone and water, further preferably methanol and / or ethanol.
9. The method according to claim 5 or 6, characterized in that: The melt mixing conditions at least include: a temperature of 150-250° C. and a time of 4-10 min.
10. Use of the aliphatic-aromatic copolyester material according to any one of claims 1 to 4 and / or the aliphatic-aromatic copolyester material prepared according to the method according to any one of claims 5 to 9 in packaging materials and / or ground films.
Citation Information
Patent Citations
Large molecular nucleating agent for poly butylenes succinate and copolyester of poly butylenes succinate and application thereof
CN102492248A
Fumaric acid-diol polyester, copolyester of fumaric acid-diol polyester, polyester nucleating agent containing fumaric acid-diol polyester and application of fumaric acid-diol polyester
CN102558521A
Rapidly crystallized PBAT material and preparation method thereof
CN108384200A
Method for preparing biodegradable aliphatic aromatic copolyester
CN111100270A
Method for synthesizing biodegradable aliphatic aromatic copolyester
CN111100272A